Pengembangan Media Flash Card Berbasis Microsoft Powerpoint pada Keterampilan Membaca Nyaring Kelas II SD - Rahmadita Putri Rusmawandani; Ikha Listyarini; Ryky Mandar Sary (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The purpose of this study was to develop Microsoft PowerPoint-based flash card media for reading aloud skills of second grade students in elementary schools that met valid and feasible criteria. In this study using the Research and Development (R&D) method of the ADDIE model which consists of five steps namely Analysis, Design, Development, Implementation, Evaluation with descriptive data analysis techniques. The media validation results reached 97% in the "very feasible" category. The results of the material validation reached 100% in the "very feasible" category. In field trials through questionnaires the teacher's response reached 100% in the "very feasible" category and in the student response questionnaire it achieved a percentage value of 98% in the "very feasible" category. Based on the percentage results, it was concluded that flash card media based on microsoft powerpoint is suitable for use by Grade II SD students. Suggestions that can be conveyed are that it is expected that teachers can use flash card media based on Microsoft PowerPoint on reading aloud skills in Indonesian language content as an alternative in teaching.